In-vitro anti tubercular activity of flowers of Couroupita guanensis L. - Ramadoss, Karthikeyan (Journal of Applied Pharmaceutical Research, 2017)
Modern civilization is facing hundreds of disorders associated with microorganisms. The natural phytochemicals fromnon-edible plants are gaining importance to fight against these disease The intention of this study is to evaluatethe ethanol and dichloromethane extracts of flower of Couroupita guianensis (Lecithydaceae) for anti-tubercular activity. The anti-tubercular activity of all the extracts of Couroupita guianensishave been evaluated againstMycobacterium tuberculosis H73Rv strain using Microplate Alamar Blue Assay (MABA). The activity wasdocumented within MIC range of 0.8 to 100ÃÂ¼g/ml. The results of MABA showed that both ethanol and dichloromethane extractexhibited significant anti-tubercular activity. The present investigation suggests that Couroupita guianensispossess remarkableanti-tubercular activity.